ETIKA (KEPRIBADIAN, PELAKSANAAN TUGAS DAN JABATAN, PELAYANAN, SESAMA REKAN) dan LEMBAGA ETIKA PROFESI di KEPOLISIAN - Lala Allifiyah; M. Irfan Maulana; A.M. Saiful Fuad; Maftuh Alfikri Rosyadi (CV. KAMPUS AKADEMIK PUBLISING, 2024)
Law enforcement by the police must be based on a code of ethics to maintain public security and comfort. The Republic of Indonesia Police (Polri) is guided by personal, state, institutional and social ethics as stated in various regulations, including Government Regulation Number 2 of 2003 and Regulation of the Head of the National Police of the Republic of Indonesia Number 14 of 2011. This ethics includes morals, responsibility, and fair service without discrimination. Strict supervision ensures that Polri members comply with a code of ethics to increase professionalism and public trust, as well as prevent violations of the law by police officers.